Comparison of clinical outcomes following treatment of chronic adult periodontitis with subgingival scaling or subgingival scaling plus metronidazole gel - Griffiths, G. S.; Smart, G. J.; Bulman, J. S.; Weiss, G.; Shrowder, J.; Newman, H. N. (Journal of clinical periodontology, 2000)
Background, aims: Conventional treatment of chronic periodontitis involves mechanical debridement of periodontal pockets. Recently, subgingival antimicrobials have been used adjunctively following such debridement. This 2‐centre study compared the clinical effects of subgingival scaling (SRP) with SRP plus subgingival application of 25% metronidazole gel, Elyzol® (SRP+gel), in patients with chronic adult periodontitis. Method: Voluntary informed written consent was obtained from 45 subjects at the Eastman (mean age 46, range 34–63) and 43 subjects at RAF Halton (mean age 47, range 34–71) who participated in this blind, randomised split‐mouth design study. All had at least 2 sites in each quadrant with probing pocket depth (PPD) 5 mm. PPD, bleeding on probing (BOP), and clinical probing attachment levels (CAL) measured using a stent, were recorded at baseline and at 1, 3, 6 and 9 months post‐therapy. After subgingival scaling of all quadrants, 2 quadrants were randomly selected to be treated with metronidazole gel. Results: A paired t‐test on baseline values showed no bias between groups. Both treatments effectively reduced the signs of periodontitis. At each follow‐up visit, reduction in PPD, CAL and BOP after the combined treatment was greater than for SRP alone. Paired t‐tests showed that the improvement in the SRP+gel group was statistically significantly better (p<0.001) than for SRP alone (mean 0.5±0.6 mm. 95% CI 0.4–0.6 mm.) Similarly, the % of sites which improved to a final pocket depth of 3 mm and the % of sites which improved over the 9 months of the study by as much as ≥2 mm were greater for SRP+gel than for SRP alone. Conclusions: At the end of the study, the mean reductions for PPD were 1.0 mm (SRP) compared to 1.5 mm (SRP+gel), and for CAL they were 0.4 mm (SRP) compared to 0.8 mm (SRP+gel), with mean difference for CAL between treatments of 0.4±0.6 mm (95% confidence intervals of 0.3–0.6 mm). The combination therapy of SRP+gel was superior to the conventional treatment of SRP alone, and these differences were maintained for 9 months.